PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR CABANG PT. ASURANSI JASINDO PALEMBANG - Nur Effen (JURNAL KOMPETITIF, 2016)
This study examined the phenomenon of employee performance  at PT. Asuransi Jasindo in Palembang. The purpose of research aims to know the influence of Leadership and motivation and  working discipline to the employees performance. The research method  used were descriptive  and verificative , and analysis method used multiple regression, multiple correlation and determination method. This study shows that the  Leadership, Motivation and  Working Discipline has significant  influence toward employee performance, but partially leadership also identifies dominant variables to influence the employee performance. Key words : Performance, Leadership, Motivation and Working Discipline.